Molecular evolution of early-onset prostate cancer identifies molecular risk markers and clinical trajectories - Gerhäuser, Clarissa; Feuerbach, Lars; Assenov, Yassen; Hübschmann, Daniel; Kuryshev, Vladimir; Weichenhan, Dieter; Toth, Reka; Lutsik, Pavlo; Lawerenz, Christian; Eils, Roland; Schlesner, Matthias; Kalle, Christof von; et al. (Cancer cell, 2018)
Summary - Identifying the earliest somatic changes in prostate cancer can give important insights into tumor evolution and aids in stratifying high- from low-risk disease. We integrated whole genome, transcriptome and methylome analysis of early-onset prostate cancers (diagnosis ≤55 years). Characterization across 292 prostate cancer genomes revealed age-related genomic alterations and a clock-like enzymatic-driven mutational process contributing to the earliest mutations in prostate cancer patients. Our integrative analysis identified four molecular subgroups, including a particularly aggressive subgroup with recurrent duplications associated with increased expression of ESRP1, which we validate in 12,000 tissue microarray tumors. Finally, we combined the patterns of molecular co-occurrence and risk-based subgroup information to deconvolve the molecular and clinical trajectories of prostate cancer from single patient samples.